Mechanism-based enantiodivergence in manganese reduction catalysis: a chiral pincer complex for the highly enantioselective hydroboration of ketones - Vasilenko, Vladislav; Blasius, Clemens K.; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie, 2017)
A manganese alkyl complex containing a chiral bis(oxazolinyl-methylidene)isoindoline pincer ligand is a precatalyst for a catalytic system of unprecedented activity and selectivity in the enantioselective hydroboration of ketones, thus producing preparatively useful chiral alcohols in excellent yields with up to greater than 99 % ee. It is applicable for both aryl alkyl and dialkyl ketone reduction under mild reaction conditions (TOF >450 h−1 at −40 °C). The earth-abundant base-metal catalyst operates at very low catalyst loadings (as low as 0.1 mol %) and with a high level of functional-group tolerance. There is evidence for the existence of two distinct mechanistic pathways for manganese-catalyzed hydride transfer and their role for enantiocontrol in the selectivity-determining step is presented.
Gesehen am 15.12.2022